In situ synthesis of nitrogen doped carbon with embedded Co@Co3O4 nanoparticles as a bifunctional electrocatalyst for oxygen reduction and oxygen evolution reactions. Issue 90 (25th October 2018) - Wang, Ying; Hu, Tianjun; Qiao, Yanting; Chen, Yan; Zhang, Limin
Abstract : The catalyst Co@Co3 O4 /N–C was in situ synthesized by simple pyrolysis and subsequent oxidative calcination, exhibiting superior ORR and OER activity. Abstract : A novel electrocatalyst of core–shell structural Co@Co3 O4 nanoparticles embedded in an N-doped carbon nanosheet (N–C) (Co@Co3 O4 /N–C) has been in situ synthesized via a simple pyrolysis and subsequent oxidative calcination. The catalyst exhibits superior bifunctional catalytic activity for the ORR and OER, which is attributed to the synergetic effect between Co and Co3 O4 and the carbon layer structure.